2016
DOI: 10.1002/anie.201602135
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Templation Generates an MII6L4 Guest‐Binding Capsule

Abstract: Pseudo‐octahedral MII 6L4 capsules result from the subcomponent self‐assembly of 2‐formylphenanthroline, threefold‐symmetric triamines, and octahedral metal ions. Whereas neutral tetrahedral guests and most of the anions investigated were observed to bind within the central cavity, tetraphenylborate anions bound on the outside, with one phenyl ring pointing into the cavity. This binding configuration is promoted by the complementary arrangement of the phenyl rings of the intercalated guest between the phenanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 55 publications
2
42
0
Order By: Relevance
“…Understanding the driving forces between ions and concave binding sites is therefore of prime importance for the supramolecular design of synthetic receptors with defined affinity and selectivity.A ccordingly,t he unexpectedly high binding affinities of superchaotropic anions and the chaotropic effect as ag eneric driving force have recently found their entry into the important area of anion recognition. [44,65,117,[131][132][133][134][135][136][137][138][139][140][141][142][143] In follow-up studies with inclusion complexes,the affinity of dodecaborate clusters to cyclodextrins (CDs) has been extended to the larger CD homologues (Figure 3) [23] as well as other borate clusters, [14,144] both in solution and in the gas phase. [14,23,24] Theb inding propensity of borate clusters has also been demonstrated for calixarenes [21] and at etrathiafulvalene host [24] as an alternative macrocyclic host (Figure 3).…”
Section: Supramolecular Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the driving forces between ions and concave binding sites is therefore of prime importance for the supramolecular design of synthetic receptors with defined affinity and selectivity.A ccordingly,t he unexpectedly high binding affinities of superchaotropic anions and the chaotropic effect as ag eneric driving force have recently found their entry into the important area of anion recognition. [44,65,117,[131][132][133][134][135][136][137][138][139][140][141][142][143] In follow-up studies with inclusion complexes,the affinity of dodecaborate clusters to cyclodextrins (CDs) has been extended to the larger CD homologues (Figure 3) [23] as well as other borate clusters, [14,144] both in solution and in the gas phase. [14,23,24] Theb inding propensity of borate clusters has also been demonstrated for calixarenes [21] and at etrathiafulvalene host [24] as an alternative macrocyclic host (Figure 3).…”
Section: Supramolecular Chemistrymentioning
confidence: 99%
“…[10,12,22,23,26,97,98] Finally,t he inclusion preference of metallo-macrocyclic cage compounds towards chaotropic anions stands out as well but has not been mechanistically rationalized in comparable detail. [142,143,152] In many cases,t he aqueous solution interactions of large anions with macrocyclic hosts are retained in their solid-state structures.I nclusion complexes are obtained (Figure 4), mostly with partial inclusion owing to the large anion sizes and frequently host-guest complexes of the 2:1t ype.T his applies to g-CD/B 12 Br 12 2À (Figure 4a), [10] g-CD/PMo 12 O 40 3À (Figure 4b), [26] and b-CD/PMo 12 O 40 3À (Figure 4c). [26] The chaotropic effect can also be exploited for the construction of more complex hybrid and hierarchical assemblies,f or example,w hen superchaotropic Dawson-type anions ( 6 ] 2+ )i nteract with g-CD (Figure 4d).…”
Section: Supramolecular Chemistrymentioning
confidence: 99%
“…However, the peripherally trapped ions ( exo ‐guest) may also play a similar role. Very recently, Nitschke's group reported that a pseudo‐octahedral M 6 L 4 capsule can only be formed in the presence of a peripherally clathrated BPh 4 − guest . Moreover, in biological systems, the TMA ion was found to significantly enhance the stability of AT‐rich DNA duplex as a result of the preferential binding to peripheral grooves composed of adenine/thymine base pairs .…”
Section: Methodsmentioning
confidence: 99%
“…2D NMR (COSY,NOESY,DOSY) also provided evidences of the formation of TMA&T in solution (Figures S13-S16). However, high-resolution mass spectrometry (HRMS) studies suggested that both tetrahedron (T, [(PO 4 ) 4 L 6 (TMA) 4 Figure S17). We hypothesized the T may partly transform to H in the diluted solutions for HRMS experiments.W ith this in mind, we checked the 1 HNMR spectrum of TMA&T,a nd at race of another set of signals (< 5%)w ere noticed even in an early saturated solution, which were assigned to the H (Figure 2a).…”
mentioning
confidence: 99%
“…[3] Supramolecular assemblies that are held together by dynamic noncovalent interactions provide the possibility to mimic stimuli-responsive behaviors of proteins.Inthe past decades,s upramolecular transformations triggered by template,s olvent, concentration, light, component and postmodification have been extensively studied. [4] These studies have significantly contributed to the understanding of the mechanisms of various structural transformations and their applications in areas such as catalysis, [5] smart materials, [6] and guest binding. [4d-e] Fori nstance,C lever and co-workers reported light-responsive guest uptake and release by aphotochromic coordination cage upon modulation of the cavity size by light.…”
mentioning
confidence: 99%